2019
DOI: 10.1111/joa.13056
|View full text |Cite
|
Sign up to set email alerts
|

Histovariability in human clavicular cortical bone microstructure and its mechanical implications

Abstract: The human clavicle (i.e. collarbone) is an unusual long bone due to its signature S‐shaped curve and variability in macrostructure observed between individuals. Because of the complex nature of how the upper limb moves, as well as due to its complex musculoskeletal arrangement, the biomechanics, in particular the mechanical loadings, of the clavicle are not fully understood. Given that bone remodeling can be influenced by bone stress, the histologic organization of Haversian bone offers a hypothesis of respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Imamura et al investigated morphological changes in the cortical bone of the femoral diaphysis with age and reported that there was no change in cortical bone thickness in men, but in women, cortical bone thickness was found to decrease with age [ 11 ]. The clavicle has a high proportion of cortical bones [ 43 ]; thus, our finding of a significant negative correlation between the BMD of the clavicle and femoral diaphysis and age in women may suggest that thinning and porosity associated with cortical bone resorption may occur in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…Imamura et al investigated morphological changes in the cortical bone of the femoral diaphysis with age and reported that there was no change in cortical bone thickness in men, but in women, cortical bone thickness was found to decrease with age [ 11 ]. The clavicle has a high proportion of cortical bones [ 43 ]; thus, our finding of a significant negative correlation between the BMD of the clavicle and femoral diaphysis and age in women may suggest that thinning and porosity associated with cortical bone resorption may occur in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…See Table S1 for abbreviations. systemic variance, genetic diversity, or some combination of all of these (Agosto & Auerbach, 2022;Crane et al, 2019;Daruwalla et al, 2010;Lambert et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These clavicle‐specific exceptions highlight that biomechanical factors influencing clavicle morphology should be investigated further. Numerous studies have identified high levels of variation in both morphology and microstructure of the clavicle, but it is still unclear if these can be attributed to elevated developmental plasticity reflecting the absence of constraint, environmental or systemic variance, genetic diversity, or some combination of all of these (Agosto & Auerbach, 2022; Crane et al, 2019; Daruwalla et al, 2010; Lambert et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The trabecularization of the cortex was a prominent feature observed in osteoporotic bone when compared to normal bone. A more detailed histological assessment of the periosteal, central and the endosteal regions further enabled identification of osteons at rest and those actively remodelling (Crane et al, 2019; Imamura et al, 2019). In our study, the definition of the two groups of osteons, those at rest and those actively remodelling, was based on arbitrarily defined intervals for the inner osteon diameter (Figure 4).…”
Section: Discussionmentioning
confidence: 99%